2018
DOI: 10.1016/j.annepidem.2018.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Consumer credit scores as a novel tool for identifying health in urban U.S. neighborhoods

Abstract: Purpose: Credit scores may operate as a socioeconomic indicator of health: they represent cumulative financial history that directly influences ability to access financial and non-financial resources related to health. Yet little is known about the relationship of credit score and health, or to traditional measures of socioeconomic position. Our objectives were to: (1) evaluate the association between area-level credit score and individual self-rated health; and (2) compare credit score to traditional markers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 20 publications
2
13
1
Order By: Relevance
“…The authors attributed this to the increased likelihood of consumer credit borrowing in areas with higher disease rates. Other recent work suggests that each SD increase in area-level credit score was associated with 26% greater odds of better individual self-rated health 5. The present study’s findings of higher risk of common chronic diseases further support this pathway.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…The authors attributed this to the increased likelihood of consumer credit borrowing in areas with higher disease rates. Other recent work suggests that each SD increase in area-level credit score was associated with 26% greater odds of better individual self-rated health 5. The present study’s findings of higher risk of common chronic diseases further support this pathway.…”
Section: Resultssupporting
confidence: 83%
“…The present study’s findings of no association between credit and chronic disease management behaviours suggest that area-level consumer credit may not reflect that areas with poorer credit comprise people with a certain set of behavioural characteristics, as some have theorised for individual’s credit scores 2 3 36. Instead, as other recent work suggests,5 area-level consumer credit may better approximate a measure of area-level SEP.…”
Section: Resultscontrasting
confidence: 70%
See 2 more Smart Citations
“…Arguably, research can often analyze the effect of gentrification on indicators such as housing and rent prices, income and racial turnover, but rarely identify the consequences of the processes. Specifically, Knapp & Dean (2018) has indicated that single direct indicators such as income or housing prices are relevant with the displacement of the low-income population; however holistic indicators such as credit scores are more appropriate to identify if displacement due to financial or economic reasons may occur. It is also important to indicate that displacement is not entirely financially dependent.…”
Section: Gentrification and New Developmentmentioning
confidence: 99%